Kajian Filosofis terkait Perlindungan Ekspresi Budaya Tradisional oleh Rezim Hak Cipta - Cheryl Yuswar; Runtung Sitepu; Dedi Harianto (University Of Bengkulu Law Journal, 2022)
This paper aims to analyze the philosophical basis for the protection of Intellectual Property Rights together with the obstacles and challenges of protecting traditional cultural expressions in Copyright regime. To achieve this goal, this legal research method uses a normative legal writing method with analytical descriptive specifications. Based on the results of the discussion, it can be concluded that the classification of the protection of traditional Indonesian cultural expressions under Law Number 28 of 2014 concerning Copyright is not appropriate because there are conflicting characteristics between copyright and traditional cultural expressions. It is necessary to further examine which Intellectual Property regime is in line with traditional cultural expressions or the preparation of a sui generis system for the purpose of protecting Indonesian's traditional cultural expressions. The placement of the protection of traditional cultural expressions in the appropriate IPR regime or sui generis system is expected to be able to maximize the economic rights that will be received by the owner and/or custodian of traditional cultural expressions. Keywords: Traditional Cultural Expression, Philosophy, Copyright